2005
DOI: 10.1074/jbc.m413878200
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-dependent Regulation of the E-cadherin Repressor Snail

Abstract: Down-regulation of E-cadherin marks the initiation of the epithelial-mesenchymal transition, a process exploited by invasive cancer cells. The zinc finger transcription factor, Snail, functions as a potent repressor of E-cadherin expression that can, acting alone or in concert with the Wnt/␤-catenin/T cell factor axis, induce an epithelial-mesenchymal transition. Although mechanisms that coordinate signaling events initiated by Snail and Wnt remain undefined, we demonstrate that Snail displays ␤-catenin-like c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
415
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 396 publications
(431 citation statements)
references
References 44 publications
13
415
1
2
Order By: Relevance
“…Previously, Monaghan et al showed distinct and elevated expression patterns of DKK-1, -2 and -3 in tissues that mediate epithelialmesenchymal transformations and suggested that they participate in the process of EMT (Monaghan et al, 1999). Additionally, regulation of snail expression and activity by Wnt could be shown (Laux et al, 2004;Bachelder et al, 2005;Yook et al, 2005). These data is supported by our findings that snail-1 expression is downregulated after expression of DKK-3.…”
Section: Discussionsupporting
confidence: 89%
“…Previously, Monaghan et al showed distinct and elevated expression patterns of DKK-1, -2 and -3 in tissues that mediate epithelialmesenchymal transformations and suggested that they participate in the process of EMT (Monaghan et al, 1999). Additionally, regulation of snail expression and activity by Wnt could be shown (Laux et al, 2004;Bachelder et al, 2005;Yook et al, 2005). These data is supported by our findings that snail-1 expression is downregulated after expression of DKK-3.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with this observation, some of these repressors have been found expressed specifically at the invasive front of human invasive hepatocellular and breast carcinoma [15,16]. The expression of these repressors seems to be highly regulated by pathways, including canonical Wnt signaling, TGF-b (see below), FGF, EGF, Stat3 and nuclear factor k-B (NFk-B) signaling [17][18][19]). Notably, Snail1 is a highly unstable protein.…”
Section: Changes In Cell-cell and Cell-matrix Adhesionmentioning
confidence: 74%
“…It is believed that during neural crest cell migration, degradation of Snail2 is controlled by polyubiquitination of the N-terminal part (Vernon and LaBonne, 2006). In addition, phosphorylation sites have been identified in Snail1 that control the nuclear localization and activity in both positive (Yang et al, 2005) and negative (Dominguez et al, 2003;Zhou et al, 2004;Yook et al, 2005) manners. However, similar sites do not appear to regulate Snail2 stability in vivo in Xenopus (Vernon and LaBonne, 2006).…”
Section: Discussionmentioning
confidence: 99%